U–Pb zircon geochronology of Proterozoic and Paleozoic rocks, North Islesboro, coastal Maine (USA): links to West Africa and Penobscottian orogenesis in southeastern Ganderia? - Reusch, Douglas N.; Holm-Denoma, Christopher S.; Slack, John F. (Atlantic Geoscience, 2018)
Within the Ganderian inlier of Penobscot Bay, coastal Maine, the Islesboro fault block occupies a central position between the St. Croix terrane of continental affinity and, to the east, the Ellsworth terrane of oceanic affinity. New field, petrographic, geochemical, and U–Pb LA-ICP-MS geochronological data on detrital and magmatic zircon grains constrain the provenance and transfer history of these terranes from Gondwana to the Appalachian margin of Laurentia. On North Islesboro, the Coombs Limestone and Hutchins Island Quartzite (new name), intruded by E-MORB amphibolite, constitute a newly recognized local inlier of Proterozoic basement. Together with the nearby Seven Hundred Acre Island Formation, these mature, carbonate-rich strata record deposition on a low-latitude passive margin. Abundant detrital zircon grains in the Hutchins Island Quartzite, all older than ca. 1.8 Ga, have a predominant population at ca. 2.0 Ga and a small peak between ca. 2.8 Ga and 2.4 Ga, an age spectrum strikingly similar to those of both the Paleoproterozoic Taghdout Quartzite in Morocco, on the West African craton, and basement rocks from Georges Bank, offshore Massachusetts. The overlying Neoproterozoic–Cambrian Islesboro Formation records a second period of extension (interstratified EMORB greenstone) synchronous with accumulation of interbedded siliciclastic and carbonate sediment, prior to recumbent folding. At the base of the moderately deformed Turtle Head Cove (new name) cover sequence, immature greywacke has a youngest zircon population of ca. 515 Ma, large late Neoproterozoic populations (ca. 624 Ma and 678 Ma), a small peak at 1.2 Ga, a moderate number of ca. 1.5 Ga to 2.0 Ga grains, and a few Late Archean grains. Compared with many similar Ganderian age spectra reported from Vermont to New Brunswick, which are all consistent with a source in either the Amazonian or West African cratons, this new age spectrum most closely resembles those from quartzites in the Grand Manaan and Brookville terranes of coastal New Brunswick. Significantly, exotic blocks lithologically indistinguishable from Proterozoic strata on Islesboro occur in the St. Croix terrane within a Lower Ordovician black shale mélange at the base of the Penobscot Formation, suggesting that the St. Croix terrane, Islesboro block, and Ellsworth terrane were initially juxtaposed by Penobscottian thrusting prior to the Middle Ordovician. Subsequently, the Islesboro block was isolated between the bounding post-Silurian, pre-Late Devonian Turtle Head and Penobscot Bay dextral strike-slip faults. Along the North Islesboro fault, a fault-bounded lens of foliated pyritic felsic volcanic and volcaniclastic rock, dated at ca. 372 Ma and containing Devonian to Archean detrital zircons, records late Paleozoic deformation recognized previously in coastal New Brunswick but not in Penobscot Bay.